Investigating the Durability and Life Cycle of Bioplastic Bags Made from Mixed Banana and Cucumber Peel Waste - KEVIN BRIZUELA (University of Mataram, 2025)
Plastic pollution is a serious environmental problem because traditional petroleum-based plastic bags cause air, water, and soil pollution and take many years to decompose. This study focused on using banana and cucumber peel waste to produce a more sustainable bioplastic as an alternative to traditional plastic bags. The objectives of this study are: (1) to develop a method for creating bioplastic bags from mixed banana and cucumber peel waste by determining the necessary steps involved in the process, (2) to determine the durability of bioplastic bags made from mixed banana and cucumber peel waste in terms of tensile strength, water resistance and biodegradability, and (3) to evaluate the life cycle of bioplastic bags made from mixed banana and cucumber peel waste in terms of estimated lifespan, biodegradation process, and recommended disposal methods. The researchers used a quasi-experimental research design through an experimental procedure by collecting, cleaning, and shredding the peels into small pieces. The materials were then mixed with agar-agar, glycerin, and borax, heated and stirred to form a mixture, poured into molds, and dried to produce bioplastic sheets. The results showed that the bioplastic could carry around 1.25 kg before tearing and had limited water resistance, as it became soft after about 2 hours in water. However, it demonstrated high biodegradability, fully decomposing within 9 days. The study concludes that bioplastic made from banana and cucumber peel waste is a promising, eco-friendly alternative to traditional plastic, although improvements are recommended to enhance its strength and durability.